Heavy element evolution in the inner regions of the Milky Way. Issue 4 (27th April 2020) - Matteucci, F; Vasini, A; Grisoni, V; Schultheis, M
ABSTRACT: We present results for the evolution of the abundances of heavy elements (O, Mg, Al, Si, K, Ca, Cr, Mn, Ni, and Fe) in the inner Galactic regions ( R GC ≤ 4 kpc). We adopt a detailed chemical evolution model already tested for the Galactic bulge and compare the results with Apache Point Observatory Galactic Evolution Experiment data. We start with a set of yields from the literature that are considered the best to reproduce the abundance patterns in the solar vicinity. We find that, in general, the predicted trends nicely reproduce the data but in some cases either the trend or the absolute values of the predicted abundances need to be corrected, even by large factors, in order to reach the best agreement. We suggest how the current stellar yields should be modified to reproduce the data and we discuss whether such corrections are reasonable in the light of the current knowledge of stellar nucleosynthesis. However, we also critically discuss the observations. Our results suggest that Si, Ca, Cr, and Ni are the elements for which the required corrections are the smallest, while for Mg and Al moderate modifications are necessary. On the other hand, O and K need the largest corrections to reproduce the observed patterns, a conclusion already reached for solar vicinity abundance patterns, with the exception of oxygen. For Mn, we apply corrections already suggested in previous works.